EcoCrisp - Aladdin, Ahmad Adamuddin; Nazir, Aqmal Hakeem; Mohammad Rosdi, Azhari (2025)
EcoCrisp is a Malaysian food manufacturing company specializing in high-quality salted egg-flavored tapioca chips, combining traditional local ingredients with modern taste trends. Targeting households and retail markets, the snacks feature convenient resealable packaging and are offered in both retail and bulk formats. EcoCrisp leverages social media, influencer collaborations, free samples, and community events to build brand awareness, supported by a dedicated management team overseeing operations, marketing, finance, and administration. With a self-funded capital of RM56,522, the company aims to distribute 10,000 packs per month in its first year and expand regionally within three years. Committed to quality, sustainability, and innovation, EcoCrisp aligns with growing consumer demand for premium, ethically sourced, and environmentally friendly snacks, positioning itself as a competitive player in the local and regional market.